Strategy to Increase Talent Retention by Using Gamification and a Holistic Approach in Increasing Talent Retention and Employee Engagement: A Systematic Literature Review - Yuhelmis; Tukiran, Martinus; Yusnita, Nancy; Sunaryo, Widodo; Hidayat, Yayan (International Journal of Social and Management Studies, 2024)
Employee retention is an important issue for organizations in various industries. The ability to retain skilled employees is critical to maintaining organizational performance, competitiveness, and sustainable growth. This systematic literature review aims to synthesize findings from various leading international journals to provide a comprehensive understanding of the factors that influence employee retention and the strategies that can be used to improve it. Talent is considered as the potential or ability of different individuals to implement organizational growth strategies and is a term that is widely discussed in the contemporary era. When handled well, talented human resources encourage organizational efforts to implement growth strategies thereby providing sustainability for the organization and encouraging economic growth. . This research uses Preferred Reporting Items for Systematic Reviews. Data was obtained from online databases, namely JSTOR, AOS-Strategi and Inovasi, John Wiley and Sons Inc, Emerald Publishing, Interscalene Publishers, SAGE Publications, University of Minnesota, Technical Publishing, Technical University of Liberec, Routledge. 65 articles were obtained. By using the keyword search "talent retention and talent management". Design/methodology/approach: This is a literature review with data from the scientific database Scopus. We found 65 results from 2006 to 2024. After removing duplicates and other search fields, we were left with 30 final documents. The analysis results obtained Talent management and talent retention should be seen as strategic business priorities and for this reason, organizations are ready to invest in the careers of these employees to increase organizational commitment. Organizations strive to retain employees by creating an engaging and enjoyable work environment, as well as implementing diverse employee retention policies to increase job satisfaction and reduce the high costs of recruiting new employees. Findings: This study provides evidence that sustainable practices in the workplace improve employee well-being and reduce environmental pollution, while providing benefits to corporate survival. Research limitations/implications: The use of other database sources besides Scopus and Web of Science can provide additional results. Practical implications: This study highlights the need for organizations to develop sustainable HRM practices to minimize negative impacts on employee well-being and capitalize on savings generated through sustainable initiatives. These findings can contribute to better corporate practices and further research development in this area. To understand strategies for increasing talent retention using gamification and a holistic approach, each of these concepts and how they can be applied in the context of increasing employee engagement and retention.